ANALISIS PENGGUNAAN MEDIA BIG BOOK DALAM MENGEMBANGKAN KEMAMPUAN BERBAHASA ANAK USIA 3-4 TAHUN - Hidayat, Yusuf; Susanti, Vina; Muztahidah, Dewi; Hajar, Siti; Muslihat, Ayi Satriani (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2023)
Language is a media for early childhood to express their feelings and experiences and communicate with others around them. This study aims to determine the impact of using big book media to develop the early childhood’s language skills aged 3-4 years. The method used in this study is a qualitative method under a descriptive approach. The results of study showed that the use of big book media empirically improve the early childhood’s language skills. The early childhood’s language skills generally develop at the level of: (1) acquiring new vocabularies, (2) fluency in pronouncing new vocabularies, (3) understanding the meaning of spoken vocabularies, and (4) being able to retell stories told by teachers based on various pictures listed in big book. In addition, the use of big book media also helps other aspects of early childhood’s development, such as: (1) cognitive aspects and (2) art aspects. In conclusion, empirically the use of big book media can help to develop the early childhood’s language skills aged 3-4 years.